Metabolite Profiling of Kirinyuh Leaf (Chromolaena Odorata L.) Ethanol Extract using UPLC-MS - Ratmini, Ni Ketut; Tedjasulaksana, Regina (Jurnal Kesehatan Gigi, 2024)
Aphthous stomatitis has become one of the oral diseases causing pain in mucous tissue. The cure of aphthous stomatitis needs flavonoid compounds that have antioxidant, antibacterial, anticancer, and antiviral activities. Kirinyuh grows well in Bali province. Although plenty of plants have grown, few investigations have been conducted on kirinyuh leaves, especially for oral disease treatment. This paper aims to examine the compounds in kirinyuh leaves to find whether it has compounds for aphthous stomatitis requirement compounds. This study was performed by metabolite profile of Kirinyuh leaves which indicates the compounds produced by its metabolic process by using the UPLC-MS instrument with ethanol extract. The metabolite profile was begun by making simplisia of the leaves with the heating process in an oven at 50°C and sifted. The powder of kirinyuh then was macerated using ethanol with ration 1:5 for 2 days and sifted with Whatman No.1, evaporated until the ethanol extract was obtained. Afterwards, the metabolite profiling was performed by UPLC-MS separating the metabolite components. The results show that there are 14 compounds in the ethanol extract of Kirinyuh leaves. The major compound in the ethanol extract of Kirinyuh leaves is [(2,2-Dimethyl-6-oxo-3,4,6,7,8,9-hexahydro-2H-cyclopenta[c]pyrano[2,3-h]chromen-10-yl)oxy]acetate with an iFit percentage of 97.56%. This compound is a pyranoflavone turnover compound including flavonoids. Besides, it is also found phenol in kirinyuh leaves. Flavonoids in kirinyuh leaves can be used as herbal plants to treat mouth ulcers. In conclusion, it is found flavonoids in Kirinyuh leaves, a compound needed to cure aphthous stomatitis.